(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2023)
The desingularization of a class of black hole space-times arising as solutions to the string equations is considered in connection with the consistency of the quantum theory and the description of nonperturbative states with quantum numbers from the particle spectrum. The geometry arising in an extreme limit of one of the singular solutions to the gravitational field equations is demonstrated to be a background of N = 2 string theory. The positivity of the masses in the particle spectrum is proven through quasilocal integrals near the resolved singularities in these limits of black hole space-times.